Library and Knowledge Management in Times of Crisis: Search for Effective Models of Activity - KOLESNYKOVA, T. O. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2023)
In this issue, our contributors share their thoughts, ideas, and doubts, describing how they and their library teams have worked hard during the recent crisis years to develop, improve, or find effective models of operation to prepare for high-level negative events and minimise catastrophic consequences. Knowledge management is definitely about university libraries, which have shifted their role from accessing and managing information to accessing, sharing and managing knowledge. The papers describe the library experience of knowledge management in times of crisis as a combination of information, communication and human resource management. The crisis experience is considered in the context of the conference "University Library at a new stage of social communications development" 2023 as the experience gained in the working library environment of universities around the world, created in the rapidly changing, chaotic and often dangerous for people’s health and life conditions of large-scale crisis events. By illustrating the challenges, surprises, and rewards we face in library and information science in different countries, we hope that the articles in this issue will provide us all with the motivation to keep going in a difficult period. At the very least, these articles will help readers to appreciate how our understanding of higher education librarianship continues to evolve in times of crisis.